Modernization using the structured system design of the Bhadra Reservoir Project, India: an intervention analysis - Sakthivadivel, Ramaswamy; Thiruvengadachari, S.; Amarasinghe, Upali A. (International Water Management Institute, 1999)
Evaluates the performance of the Bhadra Reservoir Project-before, during, and after the introduction of modernization with structured system design. Analysis focuses on water management, agricultural productivity, and farmer participation and perception. Identifies the absence of a continuing support mechanism and lack of farmer participation as the major causes for the project's decline.